Implémentation éléments finis du modèle hyperélastique anisotrope HGO - Peyraut, François; Chamoret, Dominique; Gomes, Samuel; Feng, Zhi-Qiang (European Journal of Computational Mechanics, 2010)
Anisotropic hyperelastic constitutive laws are often used to determine strain and stress in biological soft tissues such as ligaments, tendons or arterial walls. In this paper, the implementation of the HGO model in the finite element code FER is presented. Three numerical examples are studied: homogeneous uniaxial tension test where analytical solutions are available; uniaxial tension test highlighting the anisotropic behavior (contracting and swelling of the section in two perpendicular directions); contact and impact between hand and soft biological tissues in the framework of application using a virtual mannequin generator.